FRI0182 Non-biologics disease modifying anti-rheumatic drugs (nbdmards) and biologics agents acquisition and adherence among french rheumatoid arthritis patients in real life population: results from a cross-sectional study. (23rd January 2014) - Deslandre, C.; Balblanc, J.-C.; Desfleurs, E.; Antheaume, J.; Dieudé, P.
Abstract : Background: Recent meta-analysis established that the efficacy of combination therapy with a biological agent is superior to methotrexate for remission (1 ). Moreover, superiority of combination of anti-TNFa (aTNF) + nbDMARDs over aTNF monotherapy has been demonstrated. Therefore, non-adherence to nbDMARDs prescribed in combination with biologic therapy (BT) may reduce the benefit obtained with these agents. Objectives: This study investigated both acquisition and adherence to nbDMARDs and BT in real life, in patients treated either in monotherapy (MONO) or in combination (COMBO). Methods: A panel of 1000 French representative (region – turnover – population) retail pharmacies were solicited to collect prescription information on nbDMARDs and/or BT from RA patients purchasing these drugs between Nov 16 - Dec 20, 2012. In France, delivery by pharmacies of RA BT is restricted to the following subcutaneous (SC) BT: etanercept, adalimumab, certolizumab pegol, golimumab and anakinra. A record sheet was systematically assessed during dispensation at pharmacies and each included RA patient was invited to complete a self-administered questionnaire (SAQ). Adherence to nbDMARDs and/or SC BT was assessed by the Morisky Medication Adherence Scale (2 ). Identification of independent risk factors for a decrease in adherence was performed by multivariate logistic regression analysis including the following covariates: age, gender, disease duration, self-administration, prescription duration, information given on therapy and quality of life (QoL). Results: Of the 1, 050 included RA patients, 35% (n=367) received nbDMARDs in MONO, 27% (n=291) received SC BT in MONO, 23% (n=238) were treated in COMBO (SC n=226 and IV n=12) and 15% (n=154) received nbDMARDs with missing data regarding BT IV administration. The latter were excluded from further analyses. 55% (95%CI [42.6-55%]) of patients calling for SC BT (n=291/517), received it on MONO. Of the 628 filled-in SAQ which could be analysed for adherence, similar proportion of patients presenting medium/low adherence (2) to their nbDMARDs (26%, n=101/394) or their BT (27%, n=95/362) was observed, whether they were taken in MONO or COMBO. Patients on COMBO presented the same level of medium/low adherence to their nbDMARD (28%) and BT (19%). Predictive factors of medium/low adherence were identified only for the DMARD MONO population: poor QoL (P= 0.015 OR 5.31 95%CI [0, 048-0, 726]), information given on therapy by the pharmacist (P = 0.02 OR= 3.24 95%CI [1, 201-8, 754]). It should be noted that adherence may be overstated as the design of the herein study did not allow us to assess the first-fill failure rate. Conclusions: This study found that, in real world, 49% of RA patients are treated with SC BT and up to 55% received it as MONO. 28% of patients on COMBO had low adherence with nbDMARDs that may be responsible of suboptimal outcome. Better information on therapy may improve adherence. References: Kurya B, Arkema EV, Byker VP, Keystone EC Ann Rheum Dis 2010, 69:1298-304 Morisky DE, Green LW, Levine DM. Med Care 1986; 24:67-74. Disclosure of Interest: C. Deslandre Consultant for: Pfizer, Roche, J.-C. Balblanc Consultant for: Roche, Orthovisc, Paid instructor for: Pfizer, Genévrier, Wyeth, MSD, E. Desfleurs Employee of: Roche, J. Antheaume Employee of: Roche, P. Dieudé Grant/research support from: Roche, Pfizer, BMS, Consultant for: Roche, Pfizer, BMS